Verweildauer von Patienten mit hüftgelenknahen Femurfrakturen: beeinflussende Faktoren = Length of hospital stay for patients with proximal femoral fractures : influencing factors - Muhm, Markus Joachim; Weiß, Christel; Ruffing, Thomas; Winkler, Hartmut (Der Unfallchirurg, 2016)
Background: In departments of orthopedic and trauma surgery patients with proximal femoral fractures constitute the largest proportion of trauma patients. The length of stay (LOS) has economic consequences and prolonged LOS leads to a shortage in bed capacity. Objectives: In this study treatment and patient-related factors that influence the LOS of patients with proximal femoral fractures were investigated. Material and methods: Treatment and patient-related data of 242 patients (age >64 years) were recorded retrospectively and included residential aspects, legal guardianship, time of admission and surgery, hospital mortality, LOS, diagnosis, comorbidities, medication, surgical treatment, general and surgical complications, intensive care therapy and American Society of Anesthesiologists (ASA) classification. Results: Of the patients, one fifth came from a nursing home and were under supervised care or a healthcare proxy at the time of admission. Two thirds were admitted to hospital and operated on during on-call service periods. One half of the patients did not return to their previous domestic environment and were usually admitted to a nursing home. Patients who came from or were admitted to nursing homes, who were under healthcare supervision as well as patients who rapidly underwent surgery had a shorter LOS. Hospitalization and surgery during on-call service periods did not extend the LOS and showed a tendency towards reduction. Older age correlated with a longer LOS and surgical complications doubled the LOS. Discussion: Surgical treatment during on-call service periods, short preoperative waiting times and avoidance of surgical complications shortened LOS and thus had an impact on costs and bed capacity.
Gesehen am 21.08.2019
Online publiziert: 30. August 2014